Groundwater problems in urban areas proceedings of the international conference organized by the Institution of Civil Engineers and held in London, 2-3 June 1993 - Wilkinson, W. B. (Thomas Telford, 1994)
Addresses the problems associated with the changing groundwater levels - frequent deterioration of water quality, reduced water abstraction, and flooding or uplift of basements. This work provides a coverage of background information, data interpretation, details of the rising and falling groundwater levels, and possible engineering solutions.